(untitled) (Development Service Industry Management, 2025)
The main scientific research is aimed at studying methodological approaches to making economic decisions in the field of logistics flow management and modernization of the enterprise’s logistics system. It has been determined that the main goal of managing logistics flows and modernizing the enterprise’s logistics system is to ensure the continuity and timeliness of the supply of resources, products or services in the required volume, within a certain period of time and to optimal locations while simultaneously reducing total costs and increasing consumer satisfaction. This approach is a key factor in increasing the efficiency of economic activity and strengthening the competitive position of the enterprise in a dynamic market environment. It is noted that the modern concept of managing logistics flows and modernizing the enterprise’s logistics system involves the separation of material, information and financial flows. The purpose of the article is to generalize methodological approaches to making economic decisions in the field of logistics flow management and modernization of the enterprise logistics system. To this end, it is proposed for enterprises to reduce total production costs, in particular by reducing costs for transportation, storage, cargo handling and inventory management; to increase the level of customer service by reducing order fulfillment times, ensuring their accuracy and reliability, as well as through the implementation of modern service practices; improve the quality of products and services through the coordinated work of all divisions of the enterprise, the integration of management information systems and minimizing the risks of production losses and defects. The methodological approaches used in the field of logistics flow management are defined as: system-analytical approach, process-oriented approach, economic-mathematical and modeling approach, criterion-target approach and information-analytical approach. The main ways of their implementation, possibilities and advantages are indicated. Key areas of modernization of the enterprise’s logistics system have been identified, namely: digital transformation of logistics, automation of logistics processes, integration of logistics chains, environmental modernization («green logistics»).